Features and Classification of Exclamatory Sentences - Abrorova Farizabonu Aslam qizi; Asadova Gavhar Teshabayevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Exclamatory sentences represent an important component of expressive language in English. They are primarily used to convey strong emotions such as surprise, admiration, excitement, anger, and joy. Unlike other sentence types, exclamatory sentences emphasize emotional intensity and often involve specific grammatical patterns and punctuation. This article examines the features and classification of exclamatory sentences within the framework of English syntax. The purpose of the study is to analyze their structural characteristics, communicative functions, and main types. The research applies descriptive and analytical linguistic methods using examples from grammar textbooks and linguistic studies. The results show that exclamatory sentences possess distinctive grammatical forms, including structures beginning with “what” and “how,” as well as interjectional forms and emotionally intensified declarative sentences. The findings demonstrate that exclamatory constructions play an essential role in communication by allowing speakers to express emotional attitudes and evaluative meanings more effectively.